Walt Whitman & the world - Allen, Gay Wilson, 1903-1995; Folsom, Ed, 1947- (University of Iowa Press, 1995)
Celebrating the various ethnic traditions that melded to create what we now call American literature, Whitman did his best to encourage an international reaction to his work. But even he would have been startled by the multitude of ways in which his call has been answered. By tracking this wholehearted international response and reconceptualizing American literature, Walt Whitman and the World demonstrates how various cultures have appropriated an American writer who ceases to sound quite so narrowly American when he is read into other cultures' traditions.